1998
DOI: 10.2466/pms.1998.87.3.769
|View full text |Cite
|
Sign up to set email alerts
|

Distortion of Body Image among Elite Female Dancers

Abstract: To examine body image and possible distortion of body image among elite female dancers 10 members of a professional ballet company rated both current and ideal body shape. In addition, an objective measure of body composition was obtained via skinfold techniques. t tests indicated that the mean rating for current body image was significantly higher than the rating for ideal, despite the fact that body-composition measures for all subjects were in an "ideal" range according to normative standards. Analysis indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
1
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 7 publications
3
25
1
3
Order By: Relevance
“…Therefore they presents an adequate body mass index, the studies on this review claim that professional dancers present themselves more satisfied with their body image when compared to others modalities professional dancers 15 , to the common population 22 , to students 23 and to athletes 24 . Only one of the studies 10 , that investigated classical ballet and jazz professional dancers, identified that regardless the chosen modality, female professional dancers presents similar levels to body image dissatisfaction and distortion.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Therefore they presents an adequate body mass index, the studies on this review claim that professional dancers present themselves more satisfied with their body image when compared to others modalities professional dancers 15 , to the common population 22 , to students 23 and to athletes 24 . Only one of the studies 10 , that investigated classical ballet and jazz professional dancers, identified that regardless the chosen modality, female professional dancers presents similar levels to body image dissatisfaction and distortion.…”
Section: Discussionmentioning
confidence: 83%
“…The main methodological characteristics of the seven included studies in this review are presented in the Table 1, naming author/year, title, study localization, study section, population/sex/age average, periodic and qualis where it was publish 10,15,17,[21][22][23][24] . The findings show that the major number of publications happens between 2009 and 2014, and just one of the articles was publish in 1998.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Além da aplicação de testes psicológicos, foram realizadas mensurações das dobras cutâneas. Os resultados mostram que as bailarinas estavam dentro do padrão considerado ideal nas suas medidas das dobras cutâneas, mas não estavam de acordo com o seu corpo, concluindo que existe alto índice de distorção de imagem corporal em grupos profissionais de bailarinos (13) . Em relação ao nível de satisfação com a imagem corporal das bailarinas de balé clássico e de dança jazz de Porto Alegre, foi constatado que mais da metade da amostra (60%) das bailarinas de balé clássico apresentou classificação no teste BSQ no padrão de normalidade (tabela 1).…”
Section: Discussionunclassified
“…In fact, as suggested by several authors, the drive for thinness, which is present in several types of sports and is strictly related to the performance (e.g. ballet), plays a relevant role in influencing the perception of body shape [16,52,53]. Furthermore, it seems reasonable that young females who enrol in a ballet school, even if not yet affected by body uneasiness, may develop it, under the pressure of teachers and parents [54,55].…”
Section: Discussionmentioning
confidence: 99%